English as a Foreign Language (EFL) Students’ Reading Strategy Used in Comprehending Authentic Text: Students’ Preference and Students’ Perception - Safriyadin, Safriyadin; Tanduklangi, Amri; Sailan, Zalili (Journal of Language Education and Educational Technology (JLEET), 2017)
This research explored reading strategy which is used by students in learning English as a foreign language when they read authentic texts in English. This research also investigated the students’ perception towards the using of authentic materials in reading class and examined differences in the use of reading strategies when the students read authentic texts versus when they read non authentic texts.  Fifty two students of Halu Oleo University participated in this research.  Modified Survey of Reading Strategy (SORS) was used to measure the students’ general reading strategy use. One authentic reading passage and one non authentic reading passage were used for the students’ reading tasks. Questionnaire of students’ perception was used to know their perception after toward the authentic materials in reading class in English as a Foreign Language context . The results indicated that the EFL students reported using reading strategies with high frequency. Most of the students were in high category. Besides, the result shown that Problem Solving Strategy was the most category which was used by the students, followed by Global Strategy and Support strategy. Also, positive responses are shown by most of the participants toward the use of authentic materials. Another finding reported that the EFL students used more volume of reading strategies when reading authentic texts than when reading non authentic narrative texts; they frequently used some specific reading strategies when reading authentic texts, whereas they did not often use these strategies when reading non authentic texts.